Heat Transfer: Volume 2 2005
DOI: 10.1115/ht2005-72302
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Nucleation With Artificial Cavities

Abstract: Bubble incipience in artificial cavities manufactured from silicon has been studied using gas nucleation and pool boiling. Moderately wetting water and highly wetting ethanol have both been used as the bulk fluid with cylindrical cavities, as well as those with a triangle, square, and rectangle shape cross section. Nominal cavity sizes range from 8 to 60 μm. The incipience conditions observed for water using both gas nucleation and pool boiling suggest that bubble initiation originates from a concave meniscus.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 15 publications
1
10
1
Order By: Relevance
“…It is concluded that boiling incipience on the microheater is a homogeneous liquid-vapor phase change process. This is in contrast to recent observations of lowsuperheat heterogeneous nucleation on metallic surfaces of rms roughness ranging from 4 to 28 nm [1,2,3]. Following the explosive bubble incipience, the boiling process on the microheater can be maintained at much lower superheats.…”
contrasting
confidence: 51%
See 1 more Smart Citation
“…It is concluded that boiling incipience on the microheater is a homogeneous liquid-vapor phase change process. This is in contrast to recent observations of lowsuperheat heterogeneous nucleation on metallic surfaces of rms roughness ranging from 4 to 28 nm [1,2,3]. Following the explosive bubble incipience, the boiling process on the microheater can be maintained at much lower superheats.…”
contrasting
confidence: 51%
“…In contrast, Theofanous et al [1] observed low-superheat heterogeneous nucleation on a smooth titanium heater with 4 nm rms roughess submerged in water. Qi and Klausner [2,3] also observed low-superheat heterogeneous nucleation more recently on smooth brass (18 nm rms roughness) and stainless steel (28 nm rms roughness) surfaces submerged in ethanol. In contrast, Qi and…”
mentioning
confidence: 98%
“…In order to increase predictability, many researchers employed predefined artificial nucleation sites (Bonjour, Clausse & Lallemand 2000;Shoji & Takagi 2001;Zhang & Shoji 2003;Qi & Klausner 2005;Moghaddam & Kiger 2009a, amongst many others) by creating artificial cavities in the boiling substrate. The shape of these cavities differs between studies, examples are cylindrical, conical, rectangular and even triangular cavities.…”
Section: Artificial Nucleation Site Considerationsmentioning
confidence: 99%
“…Previous authors [31][32][33][34][35] considered mechanisms by which noncondensable gas could be trapped on a surface, thereby providing two-phase interfaces for heterogeneous nucleation.…”
Section: Boiling Incipiencementioning
confidence: 99%